Solubilization of hydrophobic bacteriochlorin-based photosensitizers in micelles of surfactants - E. A. Plotnikova; V. O. Stramova; N. B. Morozova; A. D. Plyutinskaya; P. V. Ostroverkhov; M. A. Grin; A. F. Mironov; R. I. Yakubovskaya; A. D. Kaprin (Biomedical Photonics)
The aim of the paper was to obtain a stable micellar emulsion of potent photosensitizer (PS) – O-propyloxime-N-propoxybacteriopurpurinimide methyl ester absorbing light in long-wave region of the spectrum (λmax = 800±2 нм). Solubilizates of the dye based on different surfactants (Kolliphor ELP, Poloxamer 407, Emuxol 268) were obtained. Taking into account the physical and chemical parameters, the most potent micellar emulsion for injection was selected and characterized. The emulsion based on Kolliphor ELP remains stable for 4 months, with no changes in the fluorescence spectrum and absorption, as well as the particle diameter.